The survival rate and growth of green catfish (Hemibagrus nemurus) fry at various water level - Juniarti, Hanifa; Taqwa, Ferdinand Hukama (Universitas Malikussaleh, 2025)
Green catfish (H. nemurus) is a type of freshwater fish that has the potential to be cultivated. Green catfish cultivation needs to be supported by ideal environmental conditions so as to produce maximum survival rate and growth. One environmental technique that can be used is water level, because the higher the water column the more energy it will uses to move and can affect the growth of green catfish fry. This research aimed to determine the best water level for survival rate and growth of green catfish fry. This research was carried out in January-February 2024 at the Fisheries Basic Laboratory, Aquaculture Study Program, Fisheries Departement, Agriculture Faculty, Universitas Sriwijaya. This research used a completely randomized design (CRD) consisting of 4 treatments and 3 replication, namely P1 with a water level of 6 cm, P2 with a water level of 12 cm, P3 with a water level of 18 cm and P4 with a water level of 24 cm. This research was carried out for 30 days. The research results showed that differences in water level a significant effect on survival rate, growth, feed efficiency and oxygen consumption level but have no significant effect on blood glucose level. The results showed that the best treatment namely P3 resulted in absolute weight growth of 3.62 g, absolute length growth of 3.60 cm, feed efficiency of 80.00%, survival of 96.30%, blood glucose level of 15,00 mg dL-1 and oxygen consumption level of 1.12 mg O2 g-1 hours-1. The water quality values for all treatments still support the survival rate of green catfish fry.Keywords: Green Catfish; Fish Growth; Survival Rate; Water Level